Sodobne protisatanistične panike - Črnič, Aleš (Teorija in praksa, 2012)
The article presents the development of the anti-satanic panic in the USA during the 1980s and early 1990s, which - as was later proven - had no real basis in any actual satanical incidents. It promotes the social constructionist approach and analyses the construction processes of urban legends about satanic abuses, deconstructs the subversion myth and the demonology which served as their basis, and analyses the broader social context within which they developed. The analysed case can serve as a more general model for understanding different counter-subversion ideologies and moral panics, which can be expected to sooner or later arise again out of the ever more persistent social crises.
Keywords: Satanism; Satanizem; Moral panic; Moralna panika; United States; Združene države Amerike; družba; society